Mogamulizumab Forecast: Clearer patients, with a slight chance of immune mayhem - Larocca, Cecilia (Clin Cancer Res, 2019)
Mogamulizumab, approved by the FDA for relapsed or refractory mycosis fungoides and Sézary syndrome, improves progression-free survival compared to vorinostat in the largest trial to date in cutaneous T-cell lymphoma, with particular efficacy in leukemic disease, but carries a risk of immune-mediated toxicities with concomitant depletion of regulatory T-cells.